Preparation method of geopolymer concrete with mixture of thermally activated muck and calcium hydroxide and prefabricated staircase

By using waste such as construction waste to prepare thermally activated waste and calcium hydroxide mixture, the problems of high energy consumption and environmental pollution in traditional concrete manufacturing are solved, and the recycling of resources and performance improvements are achieved.

CN119430762APending Publication Date: 2025-02-14SHEN ZHEN SHI JIN ZHONG JI TUAN GU FEN YOU XIAN GONG SI +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411613780.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The traditional concrete manufacturing process relies on a large amount of natural resources, which leads to high energy consumption and environmental pollution. At the same time, the waste of waste soil resources also brings ecological problems.

Method used

By utilizing waste such as construction waste, combined with alkali trigger and high-temperature calcination treatment, a thermally activated waste and calcium hydroxide mixture is prepared to reduce dependence on traditional raw materials and reduce energy consumption and emissions.

Benefits of technology

The resource utilization of waste has been achieved, greenhouse gas emissions have been reduced, dependence on natural resources has been reduced, the development of circular economy has been promoted, and the mechanical properties and durability of concrete have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430762A_ABST
    Figure CN119430762A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of geopolymer concrete prepared from a mixture of thermally activated muck and calcium hydroxide. The preparation method comprises the following steps: a, preparing raw materials; b, raw material pretreatment; c, activating; d, preparing neat paste; and e, preparing concrete. The invention further provides a prefabricated stair, and a main body material of the prefabricated stair is the geopolymer concrete of the thermally activated muck and calcium hydroxide mixture prepared by the preparation method. According to the method, the muck obtained in project earthwork excavation is used as a main raw material, waste recycling is achieved, pollution of muck waste accumulation and landfill to the environment is reduced, dependence on natural resources is reduced, and therefore the environmental protection property and sustainability of the whole preparation process are improved, the muck is used as the main raw material, and the cost is reduced. And an efficient preparation process is combined, so that the production cost of the concrete is remarkably reduced. In addition, specific additives and reinforcing agents are added, so that the cost performance and market competitiveness of the concrete are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field] The invention relates to the technical field of building materials, and in particular to a method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide and a prefabricated staircase made of geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide prepared by the preparation method. [Background technology] The traditional concrete manufacturing process not only relies on a large amount of natural resources, such as sand and stone aggregates, but also its energy consumption and environmental pollution problems in the production process have been criticized. Especially in the cement production process, data show that for every ton of Portland cement produced, about 1.5 tons of limestone and a large amount of coal and electricity are required, and a large amount of carbon dioxide is also emitted. Studies have shown that greenhouse gas emissions generated by cement production account for a considerable proportion of total human emissions, exacerbating the global greenhouse effect. In addition, the raw materials of traditional concrete mainly come from natural resources, such as sand and stone aggregates. The mining of these resources not only consumes a lot of energy, but also may lead to resource depletion and ecological damage. With the increase in the use of concrete, the demand for raw materials such as sand and stone has also continued to rise. Some areas have already experienced problems of sand and stone resource shortages and ecological damage.

[0003] In addition, with the acceleration of urbanization, the amount of waste generated by construction projects is increasing, which has brought a heavy burden to the environment. [Summary of the invention] The object of the present invention is to provide a method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide, which can utilize waste such as construction slag as raw materials, reduce dependence on traditional raw materials, reduce energy consumption and emissions in the production process, and reduce environmental pollution, aiming to solve the above-mentioned problems existing in concrete manufacturing in the prior art.

[0005] The present invention is achieved by the following technical solutions: A method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide and a prefabricated staircase comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a to obtain dry slag powder and slag particles of suitable particle size; c. Activation activation: adding the slag powder and the slag particles in step b and mixing with an alkali activator, and calcining at high temperature to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with an alkaline solution to prepare a pure slurry material; e. Concrete preparation: the clean slurry material in step d is mixed with coarse aggregate, fine aggregate and admixture to obtain heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry, and a reinforcing agent is added to the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry.

[0006] In traditional concrete production, the cement manufacturing process not only requires a lot of energy, but also releases a lot of carbon dioxide, which has an adverse impact on the environment. However, the present invention uses the slag obtained from the project earthwork excavation as the main raw material, combines alkali activator and high-temperature calcination treatment to prepare heat-activated slag and calcium hydroxide mixture geopolymer concrete, which significantly reduces the use of cement, thereby reducing greenhouse gas emissions, which is in line with the development trend of green buildings and low-carbon economy.

[0007] In addition, traditional concrete also relies on natural resources such as sand, stone and cement, the mining and use of which not only damages the environment, but may also lead to resource depletion. However, the present invention realizes the resource utilization of construction waste by effectively utilizing waste slag, reduces dependence on natural resources, and promotes the development of a circular economy.

[0008] Specifically, the slag obtained from the excavation of the project contains high moisture and impurities. The moisture can be removed by drying to make the slag reach a suitable dry state; the sieving treatment can separate the slag into particles and powders of different particle sizes, providing uniform raw materials for subsequent chemical reactions. In the active activation step, under the action of the alkaline activator, the aluminosilicate components in the slag undergo chemical reactions under high temperature conditions to generate geopolymer gels with gelling properties. In this process, the alkaline activator promotes the dissolution and repolymerization of the active components in the slag to form a three-dimensional network structure, thereby improving the activity and gelling properties of the slag. After the activated mixture is mixed with the alkaline solution, the hydroxide ions in the alkaline solution further promote the formation and stability of the geopolymer gel. Through stirring and homogenization treatment, a uniform slurry material can be obtained, which provides a good foundation for subsequent concrete configuration. In the final preparation process, after the slurry material is mixed and stirred with coarse aggregate, fine aggregate and admixture, physical and chemical reactions occur between the components to form a heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry with a dense structure and excellent performance. By adding reinforcing agents such as steel fiber, the mechanical properties and durability of concrete can be further improved, and finally a heat-activated slag and calcium hydroxide mixture geopolymer concrete with broad application prospects and market value can be obtained.

[0009] Preferably, in the present invention, the drying temperature in step b is 100-110° C., the drying time is 24 hours, and the particle size of the slag particles is less than or equal to 1.5 mm and 5-25 mm.

[0010] Drying is performed to ensure that the slag is fully dried and to remove free water and part of the bound water, thereby improving the quality and stability of subsequent concrete preparation. At the same time, this drying condition is also standardized, which is convenient for accurate control in actual operation. The selection of the particle size range of slag particles helps to improve the density and working performance of concrete. Specifically, small particles can fill the gaps between large particles and improve the density of concrete; while large particles can provide a better aggregate structure and enhance the mechanical properties of concrete.

[0011] Preferably, in the present invention, the high temperature condition in step c is 700-750° C., the calcination time is 2 hours, and the particle size of the slag particles is less than or equal to 1.5 mm.

[0012] High-temperature calcination can effectively stimulate the activity of slag, causing the aluminosilicate minerals therein to undergo phase change and activation, thereby improving the reactivity with materials such as cement. This helps to form a more stable and better-performing geopolymer gel in subsequent steps. The use of slag particles with a particle size less than or equal to 1.5 mm in step c helps to improve the calcination effect and the performance of subsequent concrete. This is because small-sized slag particles have a larger specific surface area and can more fully contact and react with the alkali activator, thereby increasing the amount and quality of geopolymer gel produced. In addition, high-temperature calcination can be carried out in a muffle furnace to ensure the uniformity and stability of the calcination process. The muffle furnace has good temperature control and regulation capabilities and can provide a constant calcination environment, thereby ensuring uniform activation of slag particles and the generation of high-quality geopolymer gel.

[0013] Preferably, in the present invention, the alkaline solution in step d is water glass, the modulus of the water glass is 2.4-2.6, the water content is 52%-58%, and the added amount is controlled between 7.5% and 10.5% in terms of weight percentage of the total amount of the liquid activator and the solid raw materials.

[0014] Water glass is a commonly used alkaline activator, and its main component is sodium silicate. Under alkaline conditions, water glass can dissolve and release silicate ions, which combine with aluminum ions in the slag to form geopolymer gel. The modulus and water content of water glass directly affect its solubility and alkalinity, and thus affect the activation effect. By selecting the appropriate modulus and water content, it is ensured that water glass has good activation performance, promotes the dissolution and polymerization reaction of active components in the slag, and thus improves the strength and durability of concrete.

[0015] Preferably, in the present invention, the water-to-solid ratio in the mixing process of step e is 25% to 35%.

[0016] Water is a necessary condition for hydration reaction. The right amount of water can promote the hydration reaction between the active ingredients in the geopolymer material and the alkaline activator to form a stable gel structure. However, too much water will increase the porosity inside the concrete and reduce the strength; too little water will affect the hydration reaction and is also not conducive to the development of strength. Therefore, controlling the water-solid ratio within the range of 25%~35% can ensure the smooth progress of the hydration reaction and obtain good strength performance.

[0017] Preferably, in the present invention, the weight mix ratio of the heat-activated slag and calcium hydroxide mixture geopolymer concrete in step e is activated mixture: water glass: fine aggregate: coarse aggregate: water = 1: 0.6~0.8: 1.8~2.0: 1.8~2.0: 0.4~0.5, the coarse aggregate is the slag particles with a particle size of 5~25 mm, and the fine aggregate is medium sand with a particle size of 1.0mm~2.0mm and a fineness modulus of 2.3~3.0.

[0018] The performance of concrete depends on the properties, proportions and interactions of its components. In the preparation process of heat-activated slag and calcium hydroxide mixture geopolymer concrete, by accurately controlling the weight mix ratio of heat-activated slag and calcium hydroxide mixture geopolymer concrete, including the ratio of activated mixture, water glass, fine aggregate, coarse aggregate and water, and selecting appropriate coarse aggregate and fine aggregate, geopolymer concrete with excellent performance and high resource utilization can be prepared.

[0019] Preferably, in the present invention, the alkaline activator in step c is calcium hydroxide.

[0020] During the high-temperature calcination process in step c, calcium hydroxide, as a strong alkaline activator, can promote the thermochemical transformation of active ingredients such as silicates in the slag. This transformation includes the decomposition of minerals, the generation of active silica-alumina oxides, etc., thereby significantly improving the reaction activity of the slag. Under the combined action of high temperature and calcium hydroxide, the formation of geopolymer gel can be promoted. Specifically, during high-temperature calcination, calcium hydroxide reacts with active silica-alumina oxides in the slag to generate precursors of geopolymer gel. These precursors will further react in the subsequent concrete preparation process. For example, when mixed with an alkaline solution (water glass) in step d, they can participate in the reaction more quickly and completely, thereby generating more geopolymer gel, which helps to improve the strength and durability of the net slurry material.

[0021] In addition, the high-temperature calcination treatment in step c not only stimulates the activity of the slag, but also changes its microstructure, such as reducing porosity and making the particle surface rougher. These changes are conducive to making it easier for the alkaline solution (water glass) to penetrate into the interior of the activated mixture when preparing the slurry in step d, fully contacting and reacting with the active ingredients therein, thereby generating a more uniform and dense geopolymer gel network. It should be added that after the activated mixture generated in step c is mixed with the alkaline solution (water glass) in step d, its highly active ingredients can quickly react with the water and alkali metal ions in the solution to generate a large amount of hydration products. These hydration products fill the pores of the slurry material, further improving its density and strength.

[0022] Preferably, in the present invention, the admixture includes S105 grade ground granulated blast furnace slag and F class fly ash, the particle size of the F class fly ash is less than 45μm, the specific surface area is 400m² / kg~450m² / kg, and the dosage range is 4~6%; the particle size of the S105 grade ground granulated blast furnace slag is less than 45μm, the specific surface area is 500m² / kg~520m² / kg, and the dosage range is 4~6%.

[0023] As active mineral admixtures, fly ash and slag mainly play a filling effect, a pozzolanic effect and a micro-aggregate effect in geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide. First, the particle size of fly ash and slag is small, which can fill the gaps between cement particles, reduce the porosity of concrete, and improve the density of concrete. Secondly, the active components in fly ash and slag can undergo secondary hydration reactions with cement hydration products (such as calcium hydroxide) to generate more hydration products (such as hydrated calcium silicate gel), which can fill the pores inside the concrete and further improve the density and strength of the concrete. Finally, the fine particles in fly ash and slag can be dispersed in the concrete as micro-aggregates, play a supporting and dispersing role, and improve the mechanical properties and durability of the concrete. In addition, the addition of fly ash and slag can also adjust the alkalinity of concrete, reduce the content of calcium hydroxide in concrete, and thus reduce the risk of alkali-aggregate reaction of concrete. At the same time, the addition of these admixtures can also improve the crack resistance of concrete, reduce shrinkage deformation, etc.

[0024] Preferably, in the present invention, the reinforcing agent is steel fiber, and the dosage range is 1.0% to 1.5%.

[0025] As a high-performance reinforcing material, steel fiber can effectively improve the tensile strength and crack resistance of concrete. Adding an appropriate amount of steel fiber to concrete can form a three-dimensional network structure, effectively preventing the expansion of cracks, thereby improving the overall tensile strength of concrete.

[0026] Specifically, when cracks appear in concrete, steel fibers can span the cracks and act as a bridge, connecting the concrete on both sides of the cracks and preventing the cracks from expanding further. When the cracks continue to expand, the steel fibers will be subjected to pull-out forces. Since the bonding force between the steel fibers and the concrete is strong, a large amount of energy is required to pull the steel fibers out. This process can effectively absorb energy and reduce the damage to the concrete. The addition of steel fibers can increase the internal constraints of the concrete and improve the compressive and tensile strengths of the concrete. At the same time, steel fibers can also refine the cracks in the concrete, reduce the width and depth of the cracks, and thus improve the durability of the concrete. In addition, the uniform distribution of steel fibers in the concrete can also effectively disperse the stress concentration phenomenon inside the concrete and improve the bearing capacity and deformation capacity of the concrete.

[0027] The present invention also provides a prefabricated staircase, comprising a staircase body, wherein the material of the staircase body is the heat-activated slag and calcium hydroxide mixture geopolymer concrete prepared by the above-mentioned heat-activated slag and calcium hydroxide mixture geopolymer concrete preparation method.

[0028] Compared with the prior art, the present invention has the following advantages: The present invention utilizes the slag obtained from the earthwork excavation of the project as the main raw material, which not only realizes the reuse of waste, reduces the pollution of the environment caused by the accumulation and landfill of slag waste, but also reduces the dependence on natural resources, thereby improving the environmental protection and sustainability of the entire preparation process. By drying, screening, activating and mixing the slag with an alkaline solution, the physical and chemical properties of the slag are effectively improved, and the slag is converted into a geopolymer concrete with excellent mechanical properties and durability. These steps work together to improve the overall performance of the final product. During the preparation process, the process parameters of each step, such as drying temperature, calcination temperature, calcination time, raw material particle size and the proportion of each component, are precisely controlled to achieve high efficiency of the process and stability of the product. Using slag as the main raw material and combining it with an efficient preparation process significantly reduces the production cost of concrete. At the same time, by adding specific admixtures and reinforcing agents, the cost performance and market competitiveness of concrete are further improved.

[0029] In summary, the present application achieves significant advantages in environmental protection, performance optimization, flexible and efficient process, cost savings and wide application through an innovative method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide and its application in the construction field.

Brief Description of the Drawings

[0031] Figure 1Schematic diagram of the preparation process of Examples 1-3 of the present invention; Figure 2 This is a schematic diagram of the structure of Embodiment 4 of the present invention; Figure 3 Prefabricated staircase concrete mise analysis of Example 4 of the present invention Figure 1 ; Figure 4 Prefabricated staircase concrete mise analysis of Example 4 of the present invention Figure 2 ; Figure 5 Mise analysis of the reinforcement of the prefabricated staircase in Example 4 of the present invention Figure 1 ; Figure 6 Mise analysis of the reinforcement of the prefabricated staircase in Example 4 of the present invention Figure 2 . [Specific implementation method] In order to make the technical problems, technical solutions and beneficial effects solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0033] Example 1 This embodiment provides a heat-activated slag and calcium hydroxide mixture geopolymer concrete, in which the weight mix ratio is: activated mixture: water glass: fine aggregate: coarse aggregate: water = 1:0.65:1.9:1.8:0.4.

[0034] The activated mixture includes slag particles, slag powder and calcium hydroxide with a particle size less than or equal to 1.5 mm; the fine aggregate is medium sand with a particle size of 1.8 mm and a fineness modulus of 2.5; and the coarse aggregate is slag particles with a particle size of 2 to 25 mm.

[0035] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and screening the slag in step a, the drying temperature is 100-110° C., and the drying time is 24 hours, so as to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and 2-25 mm; c. Activation: adding the slag powder and slag particles with a particle size of less than or equal to 1.5 mm described in step b and mixing with calcium hydroxide, and placing in a muffle furnace and calcining at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: Mix the activated mixture in step c with water glass (modulus 2.5, water content 55%) to prepare a pure slurry material; e. Concrete preparation: The slurry material described in step d is mixed with coarse aggregate (slag particles with a particle size of 2 to 25 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixture (4% of Class F fly ash and 5% of S105 grade ground granulated blast furnace slag) to obtain a geopolymer concrete slurry of a mixture of heat-activated slag and calcium hydroxide, and 1.2% of steel fiber is added to the geopolymer concrete slurry of the mixture of heat-activated slag and calcium hydroxide.

[0036] After the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry is prepared, the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for maintenance for 28 days.

[0037] Example 2 This embodiment provides a geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide, wherein the weight mix ratio is: activated mixture: water glass: fine aggregate: coarse aggregate: water = 1:0.7:2.0:1.9:0.5.

[0038] The activated mixture includes slag particles, slag powder and calcium hydroxide with a particle size less than or equal to 1.5 mm; the fine aggregate is medium sand with a particle size of 1.8 mm and a fineness modulus of 2.5; and the coarse aggregate is slag particles with a particle size of 2 to 25 mm.

[0039] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and screening the slag in step a, the drying temperature is 100-110° C., and the drying time is 24 hours, so as to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and 2-25 mm; c. Activation: adding the slag powder and slag particles with a particle size of less than or equal to 1.5 mm described in step b and mixing with calcium hydroxide, and placing in a muffle furnace and calcining at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: Mix the activated mixture in step c with water glass (modulus 2.5, water content 55%) to prepare a pure slurry material; e. Concrete preparation: The slurry material described in step d is mixed with coarse aggregate (slag particles with a particle size of 2 to 25 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixture (5% of Class F fly ash and 6% of S105 grade ground granulated blast furnace slag) to obtain a heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry, and 1.5% of steel fiber is added to the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry.

[0040] After the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry is prepared, the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for maintenance for 28 days.

[0041] Example 3 This embodiment provides a geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide, wherein the weight mix ratio is: activated mixture: water glass: fine aggregate: coarse aggregate: water = 1:0.8:1.8:1.9:0.4.

[0042] The activated mixture includes slag particles, slag powder and calcium hydroxide with a particle size less than or equal to 1.5 mm; the fine aggregate is medium sand with a particle size of 1.8 mm and a fineness modulus of 2.5; and the coarse aggregate is slag particles with a particle size of 2 to 25 mm.

[0043] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and screening the slag in step a, the drying temperature is 100-110° C., and the drying time is 24 hours, so as to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and 2-25 mm; c. Activation: adding the slag powder and slag particles with a particle size of less than or equal to 1.5 mm described in step b and mixing with calcium hydroxide, and placing in a muffle furnace and calcining at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: Mix the activated mixture in step c with water glass (modulus 2.5, water content 55%) to prepare a pure slurry material; e. Concrete preparation: the slurry material described in step d is mixed with coarse aggregate (slag particles with a particle size of 2 to 25 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixture (6% of Class F fly ash and 6% of S105 grade ground granulated blast furnace slag) to obtain a heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry, and 1.0% of steel fiber is added to the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry.

[0044] After the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry is prepared, the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for maintenance for 28 days.

[0045] Performance test: The heat-activated slag and calcium hydroxide mixture geopolymer concrete prepared in Examples 1-3 was tested for setting time of concrete slurry according to the Standard for Test Methods for Performance of Ordinary Concrete Mixtures (GB / T 50080-2016), and the 7d compressive strength and 28d compressive strength of concrete were tested according to the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T50081-2019). The test results are shown in Table 1.

[0046] Table 1 Performance test results of geopolymer concrete made of mixture of heat-activated slag and calcium hydroxide

[0047] As shown in Table 1, the 7d average compressive strength of Examples 1-3 can reach up to 26.1MPa, and the 28d average compressive strength can reach up to 38.3MPa, with excellent mechanical properties. The project waste slag as the main raw material of concrete can meet the national standards and can be used as a substitute for ordinary concrete in most engineering projects, which can significantly reduce the dependence on traditional concrete raw materials (such as sand and stone aggregates). It not only reduces the energy consumption in the process of raw material mining, but also reduces the emission of related greenhouse gases (such as carbon dioxide), thereby effectively alleviating the global greenhouse effect, realizing the reasonable secondary use of industrial waste resources (i.e. slag), promoting the recycling of resources, saving construction costs, and greatly reducing the transportation and processing costs of construction slag, bringing significant economic benefits to enterprises.

[0048] Embodiment 4, this embodiment provides a prefabricated staircase, including a staircase body 1, wherein the material of the staircase body 1 is the heat-activated slag and calcium hydroxide mixture geopolymer concrete prepared by the heat-activated slag and calcium hydroxide mixture geopolymer concrete preparation method proposed in Embodiments 1-3. In actual production, the prefabricated staircase is mass-produced in a factory through the configured heat-activated slag and calcium hydroxide mixture geopolymer concrete ratio, and the factory realizes the process from receiving the engineering slag, drying, screening and classification, high-temperature calcination to activate the activity of the mixture, and then forming the heat-activated slag and calcium hydroxide mixture geopolymer concrete after being excited by an alkaline activator, and the factory adopts high-temperature curing to realize the whole production process of the engineering prefabricated components, and finally prefabricated into the prefabricated staircase of this embodiment.

[0049] In this embodiment, the use of prefabricated stairs using geopolymer concrete mixed with heat-activated slag and calcium hydroxide as the main material in the building structure can be simulated and analyzed by finite element analysis software abaqus. Figures 2 to 5 As shown, Figures 2 to 3 This is the precast staircase concrete mise analysis diagram proposed in this embodiment. Figures 4 to 5 This is the reinforcement Mise analysis diagram of the prefabricated stairs. It can be seen from the figure that the overall strength of the prefabricated stairs made of heat-activated slag and calcium hydroxide mixture geopolymer concrete is equivalent to that of C30 concrete, which can realize the application and promotion of heat-activated slag and calcium hydroxide mixture geopolymer concrete components.

[0050] The above are implementation methods provided in combination with specific contents, and it is not intended that the specific implementation of this application is limited to these descriptions. Any method structure similar to the present application, or a number of technical deductions or replacements based on the concept of the present application, should be considered as the protection scope of this application.

Claims

1. A method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide, characterized in that: The following steps are involved: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a to obtain dry slag powder and slag particles of suitable particle size; c. Activation activation: adding the slag powder and the slag particles in step b and mixing with an alkali activator, and calcining at high temperature to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with an alkaline solution to prepare a pure slurry material; e. Concrete preparation: the clean slurry material in step d is mixed with coarse aggregate, fine aggregate and admixture to obtain heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry, and a reinforcing agent is added to the heat-activated slag and calcium hydroxide mixture geopolymer concrete slurry.

2. The method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide according to claim 1, characterized in that: In step b, the drying temperature is 100-110° C., the drying time is 24 hours, and the particle size of the slag particles is less than or equal to 1.5 mm and 5-25 mm.

3. The method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide according to claim 1, characterized in that: In step c, the high temperature condition is 700-750°C, the calcination time is 2 hours, and the particle size of the slag particles is less than or equal to 1.5 mm.

4. The method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide according to claim 1, characterized in that: In step d, the alkaline solution is water glass, the modulus of the water glass is 2.4-2.6, the water content is 52%-58%, and the amount added is controlled between 7.5% and 10.5% in terms of weight percentage of the total amount of the liquid activator and the solid raw materials.

5. The method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide according to claim 1, characterized in that: In the mixing process of step e, the water-to-solid ratio is 25% to 35%.

6. The method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide according to claim 1, characterized in that: In step e, the weight ratio of the heat-activated slag and calcium hydroxide mixture geopolymer concrete is activated mixture: water glass: fine aggregate: coarse aggregate: water = 1: 0.6~0.8: 1.8~2.0: 1.8~2.0: 0.4~0.5, the coarse aggregate is the slag particles with a particle size of 5~25 mm, and the fine aggregate is medium sand with a particle size of 1.0mm~2.0mm and a fineness modulus of 2.3~3.

0.

7. The method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide according to claim 1, characterized in that: The alkaline activator in step c is calcium hydroxide.

8. The method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide according to claim 1, characterized in that: The admixtures include S105 grade ground granulated blast furnace slag and F class fly ash. The particle size of the F class fly ash is less than 45 μm, its specific surface area is 400 m² / kg~450 m² / kg, and the admixture range is 4~6%; the particle size of the S105 grade ground granulated blast furnace slag is less than 45 μm, its specific surface area is 500 m² / kg~520 m² / kg, and the admixture range is 4~6%.

9. The method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide according to claim 1, characterized in that: The reinforcing agent is steel fiber, and the dosage range is 1.0% to 1.5%.

10. A prefabricated staircase, characterized in that: The invention comprises a staircase body (1), wherein the material of the staircase body (1) is a heat-activated slag and calcium hydroxide mixture geopolymer concrete prepared by the method for preparing a heat-activated slag and calcium hydroxide mixture geopolymer concrete according to any one of claims 1 to 9.